Stock Market Valuation in Sharia Compliance Lens: An Evaluation of the Intrinsic Value of Sharia-Compliant Stocks - Ryandono, Muhamad Nafik Hadi; Wijayanti, Ida; Wardhana, Akhmad Kusuma; Imron, Mochamad Ali; Miraj, Denizar Abdurrahman (Journal of Posthumanism, 2025)
Sharia compliance has become increasingly important in the financial world, especially within the context of stock market valuation. This study aims to evaluate the intrinsic value of Sharia-compliant stocks through a set of variables that reflect Sharia-compliant principles. This study used the panel data regression with Arbitrage Pricing Theory (APT) to understand the findings and analysis. The study also describes its model with full inclusion of tables and all statistics, explaining the study's contribution in that respect. The variables used in this study include the intrinsic value of Sharia stock, Financing to Total Assets Ratio (FTAR), on-sharia compliant income Ratio (NSCR), Cash Participation in Bank Conventional Ratio (CCR), Interest Financing to total Financing Ratio (IFR), Salary costs to operating costs Ratio (SOCR), and Philanthropic Fund Ratio (PFR). The study highlights the importance of evaluating stock market valuation through a Sharia-compliant lens. Sharia compliance principles emphasize ethical and moral values that promote social responsibility and fair practices. The findings of this study can inform investors, policymakers, and financial institutions about investments in Sharia-compliant stocks, as these stocks provide a comprehensive evaluation of intrinsic value. The study's approach can serve as a useful methodology for future research in Sharia-compliant finance.